(untitled) - Stern, Kingsley R. (Boston, 2008)
Assuming little prior scientific knowledge on the part of the student, this book includes sufficient information for some shorter introductory botany courses open to both majors and nonmajors, and is arranged so that certain sections can be omitted without disrupting the overall continuity of the course.
Keywords: Botany,Thực vật học